Towards inoculant development for Bambara groundnut (Vigna subterranean (L.) Verdc) pulse crop production in Namibia - Sarkar, Abhijit; Fwanyanga, Felicitas M.; Horn, Lydia N.; Welzel, Sina; Diederichs, Marco; Kerk, Luca Jonas; Zimmermann, Meret; Reinhold-Hurek, Barbara (Frontiers in Plant Science, 2023)
Globally expanding population together with climate change pose a risk to the availability of food for mankind. Bambara groundnut (BGN) (Vigna subterranea (L.) Verdc) is a neglected, relatively drought tolerant native legume of Sub-Saharan Africa that can may become a successful food crop because of its nutritional quality and climate smart features. Nitrogen fixation from root nodule symbiosis with climate-adapted rhizobial symbionts can contribute nitrogen and organic material in nutrient poor soil and improve yields. However, high soil temperature and drought often reduces the abundance of native rhizobia in such soil. Therefore, formulation of climate smart biofertilizers has the potential to improve farming of BGN at low cost in a sustainable manner. Thus, the effect of seven Bradyrhizobium spp. strains native to Namibia, including B. vignae and B. subterraneum, were tested on three Namibian BGN varieties (red, brown, cream) in greenhouse pot experiments in Namibia, using soil from the target region Kavango. Each variety was treated with a mixed inoculant consisting of seven preselected strains (“MK”) as well as with a promising single inoculant strain. The results revealed that in all three varieties, the two inoculants (mixed or single) outperformed the non-inoculated cultivars in terms of shoot dry weight by up to 70%; the mixed inoculant treatment performed significantly better (p  0.05) in all cases compared to the single inoculant used. To test whether the inoculant strains established in root nodules, they were identified by sequence analysis. In many cases the indigenous strains of Kavango soil outcompeted the inoculant strains of the mix for nodule occupancy, depending on BGN variety. As a further preselection, each of the individual strains of the mix was used to inoculate the three varieties under sterile conditions in a phytotron. The agronomic trait and root nodulation response of the host plant inoculations strongly differed with the BGN variety. Even competitiveness in nodule occupancy without involving any indigenous strains from soil differed and depended strictly on the variety. Therefore, severe differences in symbiont-plant interactions appear to occur in BGN depending on the plant variety, demanding for coupling of breeding efforts with selecting efficient inoculant strains.